2014
DOI: 10.4172/2157-7439.1000198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lavander Essential Oil Addition on Passion Fruit Oil Nanoemulsions: Stability and In vivo Study

Abstract: Nanoemulsions present droplets between 20 to 500 nm. It can be obtained by high-energy or low-energy methods. The aim of this study was to evaluate the influence of Lavander Essential Oil (LEO) in the formation of Passion Fruit Oil nanoemulsions, water and a blend of nonionic surfactants. The results show a reduction in droplet size with the addition of LEO, which can be explained by the possibility of essential oil molecules to penetrate into the interface and change their properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…These results indicate the presence of signs of instability in the system with increasing temperature (45 ± 5 • C). These results corroborate to the results of [3] in the development of passion fruit and lavender oil nanoemulsions.…”
Section: Formulation Studiessupporting
confidence: 91%
See 2 more Smart Citations
“…These results indicate the presence of signs of instability in the system with increasing temperature (45 ± 5 • C). These results corroborate to the results of [3] in the development of passion fruit and lavender oil nanoemulsions.…”
Section: Formulation Studiessupporting
confidence: 91%
“…These results corroborate to the results of [3] in the development of passion fruit and lavender oil nanoemulsions. presence of signs of instability in the system with increasing temperature (45 ± 5 °C).…”
Section: Formulation Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…Several other studies concluded that VE acetate can act as an additional surfactant due to its ability to position at the oil-water interface. It was observed that it can decrease droplet size of the nanoemulsions and improve their physical stability (Gledovic et al 2020, Rocha-Filho et al, 2014Teo et al, 2010). For example, in the latter study, VE acetate and Pluronic F-68 were found to co-stabilize the formulations and nanoemulsions with droplet size ~ 94 nm, physically stable for 4 weeks at > 45˚C were obtained.…”
Section: • Introduction Of Lipophilic And/or Hydrophilic Antioxidantsmentioning
confidence: 75%
“…However, when using higher amounts of surfactants, the formed micelles can sometimes facilitate the migration of smaller oil droplets to the larger ones (Ostwald ripening), or an excess of surfactant may alter the properties of the interfacial layer, thereby enhancing coalescence (Chuesiang et al, 2018). Lipophilic non-ionic surfactants Span 80 (Sorbitan monooleate) and Span 20 (Sorbitan monolaurate) are also commonly used to decrease the HLB value of the Tween-Span mixture and to match it with the HLB of natural oils, leading to a decrease in droplet size and an increase in physical and/or chemical stability (Chong et al, 2018;Zhong et al, 2017;Rocha-Filho et al, 2014). However, looking at the available data presented in Table 4.1, it can be concluded that lecithin and Spans, without additional stabilisers, were not particularly effective at inhibiting chemical instability at elevated temperatures.…”
Section: Stability Of Antioxidant-loaded Nanoemulsionsmentioning
confidence: 99%